Faktor-Faktor yang Mempengaruhi Adopsi Inovasi SITT Sapi Potong di Kabupaten Bengkulu Selatan - Linda Harta; Satria Putra Utama; M Zulkarnain Yuliarso (Jurnal Penyuluhan, 2021)
Adoption of the crop-livestock system (CLS) technology innovation is influenced by internal and external factors of farmers. The purpose of this study was to determine the influencing factors of CLS adoption technology innovation for beef cattle in South Bengkulu Regency. The research was carried out from January to April 2020 at the location of the Integrated intensive livestock village (Integrated ILV) in South Bengkulu Regency located at 5 villages. Data were collected through a census involving 73 farmers i.e. farmers’ characteristics, performance of the extension agents, attributes of CLS innovation, communication channels, farmers' attitudes towards innovation, and the farmer adoption of CLS. Data analysis using SEM-PLS method. The results showed that farmer adoption of CLS was significantly influenced by the performance variables of the extension agents and the attributes of innovation, but not influenced by communication behavior and farmers’ attitudes.